Outcomes of Biventricular Mechanical Support Patients Discharged to Home to Await Heart Transplantation. Issue 4 (July 2015) - Creaser, Julie W.; Rourke, Darlene; Vandenbogaart, Elizabeth; Chaker, Tamara; Nsair, Ali; Cheng, Richard; Fonarow, Gregg; Livingston, Nancy; Howell, Elan; Huie, Newman; Baas, Arnold S.; Deng, Mario; et al.
<x xml:space="preserve">Abstract</x> Background: The use of left ventricular assist devices has grown rapidly in recent years for patients with end-stage heart failure. A significant proportion of patients require both left- and right-sided support with biventricular assist devices (BiVADs) as a bridge to transplantation. Traditionally, these patients have waited in the hospital until they receive a transplant. Purpose: The aim of this study was to characterize the clinical course of BiVAD patients discharged to home to await heart transplantation. Methods: Between November 2009 and July 2011, 24 adult patients underwent Thoratec paracorporeal BiVAD placement at the University of California Los Angeles, all with an Interagency Registry for Mechanically Assisted Circulatory Support score 1 or 2. The disposition, complications, and rehospitalizations of these subjects were retrospectively reviewed. Results: Fourteen of the 24 patients were successfully discharged to home, with a mean time of 60 ± 27 days from BiVAD implantation to discharge. Ninety-three percent (13/14) of the patients sent home went on to be transplanted. Eleven of the 14 (79%) came in from home to receive their transplant. The mean time from BiVAD implantation to transplantation was 100 ± 65 days. Of the 14 patients discharged to home, there were 18 readmissions in 8 patients. Conclusion: In this small single-center review, we found that complex medical patients with BiVADs can be discharged to home and can await a heart transplant from home under the close management of multidisciplinary acute care and outpatient teams.